1998
DOI: 10.1007/bf02495662
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids fromAbies species

Abstract: Triterpenoids from Abies species 22.* Isolation of the cyclic tautomer of (24Z)-3,23-dioxolanosta-8,24-dien-26-oic acid, a new component of the acidic fraction of the extract from Siberian fir needleA new component, namely, the cyclic tautomer of previously unknown (242)-3,23-dioxolanosta-8,24-dien-26-oic acid, was isolated from the acidic fraction of the extract from Siberian fir needle. The structure of the title compound was established based on the IH NMR and circular dichroism spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The typical NMR data (δ H 1.92, s, 6.75, brs; δ C 10.5, 105.4, 147.2, 132.1, 171.9) indicated the presence of an α,β-unsaturated-γ-lactone moiety (ring F), which was verified by the following HMBC data: H-24 with C-23 and C-26; and H-27 with C-26 and C-24. In addition, the HMBC cross peaks from H-22 to C-17 as well as from H-22 to C-23, taking the remaining oxygen atoms into consideration, revealed that rings D and F were connected via C(20)–C(22) bond and a rare oxygen bridge between C-16 and C-23 forming ring E. The rings E and F were linked via a dioxygen-bearing sp 3 quaternary carbon (C-23).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The typical NMR data (δ H 1.92, s, 6.75, brs; δ C 10.5, 105.4, 147.2, 132.1, 171.9) indicated the presence of an α,β-unsaturated-γ-lactone moiety (ring F), which was verified by the following HMBC data: H-24 with C-23 and C-26; and H-27 with C-26 and C-24. In addition, the HMBC cross peaks from H-22 to C-17 as well as from H-22 to C-23, taking the remaining oxygen atoms into consideration, revealed that rings D and F were connected via C(20)–C(22) bond and a rare oxygen bridge between C-16 and C-23 forming ring E. The rings E and F were linked via a dioxygen-bearing sp 3 quaternary carbon (C-23).…”
mentioning
confidence: 61%
“…A. chensiensis is one of the Chinese endemic plants mainly distributed over Shanxi and Hubei provinces of the People’s Republic of China . A number of nature products have been found in the previous studies. , As part of a program to search for unique and bioactive secondary metabolites, two novel rearranged triterpenoids, spirochensilides A ( 1 ) and B ( 2 ), along with a known biogenetically related compound 3 (23-hydroxy-3-oxolanosta-8,24-dien-26,23-olide), were isolated from the leaves and twigs of A. chensiensis . Herein, we report the isolation and structural elucidation of these novel compounds.…”
mentioning
confidence: 99%
“…Then, the EtOAc fraction was separated using various chromatographic techniques, producing nine new cycloartane triterpenoids (1, 2, 4, 7, 8, 12, 15, 17, and 18) and two new tetraterpenoids (24 and 25), together with 14 previously reported triterpenoids. These known compounds were identified as mangiferonic acid (3), 7 (3β,23S)-dihydroxycycloart-24E-en-26-oic acid (5), 8 magniferolic acid (6), 9 isomangiferolic acid (9), 10 abifarine R (10), 11 15β-hydroxy-3α-methoxycycloarten-24E-en-26-oic acid (11), 12 (23R)-3αhydroxy-9,19-cyclo-9β-lanost-24-en-26,23-olide (13), 13 euphorbatrine G (14), 14 (24S*,25R*)-cycloartane-3β,24,25,26tetrol (16), 15 24(R)-9,19-cyclolanost-3-one-24,25-diol (19), 16 (24R)-cycloartane-3β,24,25-triol (20), 17 abifarine K (21), 11 23-hydroxy-3-oxolanosta-8,24-dien-23,26-olide (22), 18 and neoabiestrine D (23), 19 based on the comparison of their spectroscopic data with the literature values (Figure 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The lanostane lactones, 12, 13, 30 and 14, 31 have been isolated from Abies sibirica. Clavaric acid 15, from the fungus Clavariadelphus truncatus, has been shown to inhibit farnesyl-protein transferase.…”
Section: The Fusidane-lanostane Groupmentioning
confidence: 99%